2004
DOI: 10.1073/pnas.0407204101
|View full text |Cite
|
Sign up to set email alerts
|

Guiding neuronal development with in situ microfabrication

Abstract: We report the ability to modify microscopic 3D topographies within dissociated cultures, providing a means to alter the development of neurons as they extend neurites and establish interconnections. In this approach, multiphoton excitation is used to focally excite noncytotoxic photosensitizers that promote protein crosslinking, such as BSA, into matrices having feature sizes >250 nm. Barriers, growth lanes, and pinning structures comprised of crosslinked proteins are fabricated under conditions that do not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
146
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 30 publications
1
146
0
5
Order By: Relevance
“…Taken together, these results imply that a broad range of hydrogel swelling profiles will be possible by judicious selection [or engineering (37)] of protein building blocks. Further, protein matrices composed of avidin, which we previously have demonstrated retain biotin-binding functionality (23)(24)(25), showed attenuated swelling in acid and denaturant solutions in the biotinbound state compared with the unbound state ( Fig. 2d and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together, these results imply that a broad range of hydrogel swelling profiles will be possible by judicious selection [or engineering (37)] of protein building blocks. Further, protein matrices composed of avidin, which we previously have demonstrated retain biotin-binding functionality (23)(24)(25), showed attenuated swelling in acid and denaturant solutions in the biotinbound state compared with the unbound state ( Fig. 2d and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that direct-write protein matrices can retain ligand-binding and catalytic functionality similar to that of their component proteins (23)(24)(25)(26)(27), implying that native electrostatic and hydrophobic interactions governing protein conformation remain significantly intact within microstructures. However, at pH extremes, unfavorable electrostatic interactions can disrupt the native state and result in protein unfolding (31,32).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By scanning the fabrication voxel through reagent solution, complex three-dimensional microscale objects 1,5 have been produced with lateral feature sizes as small as ∼120 nm using synthetic materials 1 and ∼250 nm using proteins. 4 Figure 1A demonstrates our approach for mask-directed multiphoton lithography. Here, light from a femtosecond titanium: sapphire (76 kHz) laser is sent through an unmodified confocal scan box to raster the beam in a rectangular pattern at a focal plane positioned between the scan box and an inverted microscope.…”
mentioning
confidence: 99%